“Mazing the Minotaur Back”: Subjectivity, Agency, and Counter-Surveillance in Ali Smith’s How to Be Both (2014) - Wrobel, Claire (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2026)
This article discusses the formal choices and strategies adopted by Scottish author Ali Smith in her novel How to Be Both (2014) to contribute to our understanding of contemporary surveillance practices, delve into the complexities of subjective experiences of surveillance—especially in its gendered aspects—and explore the possibility of agency and resistance. Such strategies include mobilizing seemingly outdated genres, adopting a non-linear narrative structure that produces a defamiliarizing effect, and drawing on modes such as humour and irony. When the novel appeared in 2014, Edward Snowden’s revelations on mass state surveillance were very much on readers’ minds. How to Be Both addresses the challenges raised by the scandal in terms of representation and conceptualization by drawing on generic resources such as the spy novel or the film noir, developing a subplot around one of the protagonists’ deceased mother, who may or may not have been spied upon in connection with her political activism. But the novel also goes beyond the immediate context of the Snowden revelations by following the mourning daughter in whose daily life surveillance is deeply imbricated. Through their subjective experiences, the novel raises unsettling—and deliberately unsettled—questions about the entanglement of surveillance with desire, the longing for recognition and interpersonal connections, and the possibility of forms of counter-surveillance that articulate the individual and collective levels, and that are playfully referred to as “mazing the minotaur back.”